The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s00425-010-1323-6
|View full text |Cite
|
Sign up to set email alerts
|

Selenium accumulation in lettuce germplasm

Abstract: Selenium (Se) is an essential micronutrient for animals and humans. Increasing Se content in food crops offers an effective approach to reduce the widespread selenium deficiency problem in many parts of the world. In this study, we evaluated 30 diverse accessions of lettuce (Lactuca sativa L.) for their capacity to accumulate Se and their responses to different forms of Se in terms of plant growth, nutritional characteristics, and gene expression. Lettuce accessions responded differently to selenate and seleni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
60
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 46 publications
11
60
0
8
Order By: Relevance
“…Nesse sentido, Hopper & Parker (1999) relataram que o selenito é rapidamente convertido em formas orgânicas de Se, as quais são incorporadas em proteínas em substituição ao S, causando toxidez mais rapidamente quando comparado ao selenato. Os resultados encontrados no presente estudo são semelhantes ao observado por Ríos et al (2008), ao avaliarem a biofortificação com Se e a indução da capacidade antioxidante em plantas de alface utilizando o selenato e selenito, e ao verificado por Ramos et al (2011), ao estudarem a variação genotípica em diversos germoplasmas de alface.…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Nesse sentido, Hopper & Parker (1999) relataram que o selenito é rapidamente convertido em formas orgânicas de Se, as quais são incorporadas em proteínas em substituição ao S, causando toxidez mais rapidamente quando comparado ao selenato. Os resultados encontrados no presente estudo são semelhantes ao observado por Ríos et al (2008), ao avaliarem a biofortificação com Se e a indução da capacidade antioxidante em plantas de alface utilizando o selenato e selenito, e ao verificado por Ramos et al (2011), ao estudarem a variação genotípica em diversos germoplasmas de alface.…”
Section: Resultsunclassified
“…Entretanto, a essencialidade desse elemento para as plantas ainda é motivo de controvérsia no meio científico (Zhu et al, 2009;PilonSmits & Quinn, 2010). Há relatos que o Se pode ajudar as plantas a se manterem por mais tempo fisiologicamente ativas, aumentando a produção vegetal (Hartikainen et al, 2000;Lyons et al 2009;Ramos et al, 2011).…”
Section: Introductionunclassified
“…Although selenium has not been demonstrated to be essential in plants, many studies show that, when supplied in low doses, Se benefits plant growth and production (Kápolna et al, 2009;Ramos et al, 2011;Boldrin et al, 2013;Zhu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the success of biofortification with Se in lettuce, rice, wheat and broccoli (Ramos et al, 2011;Boldrin et al, 2013;Zembala et al, 2010;Ávila et al, 2014). In this sense, carrot (Daucus carota L.), a widely consumed vegetable, renders great potential to this practice, since it presents a high content of carotenoids.…”
Section: Introductionmentioning
confidence: 99%
“…The role of this element in plants is still controversial Pilon-Smits and Quinn, 2010), yet some studies seem to indicate that selenium maintain plants physiologically active for longer life periods, which in some cases determines an increasing crop production (Hartikainen et al, 2000;Lyons et al, 2009;Ramos et al, 2011). Nevertheless, is worth emphasizing that, in biofortification programs the form of selenium applied must be taken into account (Zhang and Sparks, 1990), since plant species not have different uptake capacities, but also the accumulation of selenium forms (selenite, selenite and organic forms of selenium) in the soil can vary (Kabata-Pendias, 1999 cf.…”
Section: Introductionmentioning
confidence: 99%